Rapid multiplication of Safed musli (Chlorophytum borivilianum) through shoot proliferation - Kemat, Nurashikin; Abdul Kadir, Mihdzar; Abdullah, Nur Ashikin Psyquay; Ashraf, Farshad (Academic Journals, 2010)
Young shoot buds were used as explants for rapid multiplication of Safed musli (Chlorophytum borivilianum). The explants were cultured onto medium containing basal salts of Murashige and Skoog (MS) and various concentrations of 6-benzylaminopurine (BAP) and kinetin (KIN) for shoot induction. Treatment containing 3.0 mg/l BAP produced the highest mean number of shoots per explants (18.90) and a mean length of shoots (6.0 cm) after 28 days of culture. Regenerated shoots were successfully rooted on MS medium supplemented with 1.0 mg/l indole-3-butyric acid (IBA) and 30 g/l sucrose. For ex vitro establishment, well-rooted plantlets were transferred in potting medium containing vermiculite : organic matters (1:1).